Efficacy of downtitration or treatment withdrawal compared with continuous dosing after successful treatment with baricitinib in patients with moderate-to-severe atopic dermatitis in a randomized substudy from the long-term extension study BREEZE-AD3. (17th November 2022) - Reich, Kristian; Simpson, Eric; Wollenberg, Andreas; Bissonnette, Robert; Abe, Masatoshi; Cardillo, Tracy; Janes, Jonathan; Sun, Luna; Chen, Sherry; Silverberg, Jonathan I
Abstract: Background: Baricitinib, an oral, selective Janus kinase 1/2 inhibitor, demonstrated long-term efficacy in moderate-to-severe atopic dermatitis in an ongoing double-blind, phase III, long-term extension study, BREEZE-AD3 (NCT03334435). Objectives: To evaluate the efficacy and safety of downtitration and treatment withdrawal in a substudy of BREEZE-AD3. Methods: The substudy included patients ( N = 526) treated with baricitinib 4 mg or 2 mg at entry into BREEZE-AD3 who achieved a validated Investigator Global Assessment for Atopic Dermatitis (vIGA-AD ® ) scale score of 0 (clear), 1 (almost clear) or 2 (mild) at week 52. Patients treated with baricitinib 4 mg were rerandomized to baricitinib 4 mg (continuous dosing), baricitinib 2 mg (downtitration) or placebo (treatment withdrawal, 4-mg cohort), and patients treated with baricitinib 2 mg were rerandomized to baricitinib 2 mg (continuous dosing), baricitinib 1 mg (downtitration), or placebo (treatment withdrawal, 2-mg cohort). After 16 weeks, we assessed the proportion of patients with vIGA-AD ® 0/1, vIGA-AD ® 0/1/2, vIGA-AD ® ≥ 3 (loss of response; criterion to readminister the original baricitinib dose) and for patients who were readministered the original baricitinib dose, we assessed the proportion of patients who recaptured vIGA-AD ® 0/1/2 within 16 weeks of treatment readministration (patients in the continuous dosing maintained the same dose). Results: For the continuous dosing, downtitration, and treatment withdrawal groups 51%, 45% and 30% of patients in the 4-mg cohort achieved vIGA-AD ® 0/1 and 87%, 61% and 50% of patients achieved vIGA-AD ® 0/1/2, respectively. For the 2-mg cohort, the respective proportions of patients were 48%, 42% and 25% for vIGA-AD ® 0/1 and 92%, 71% and 45% for vIGA-AD ® 0/1/2. The respective proportions of patients with vIGA-AD ® ≥ 3 were 39%, 49% and 56% in the 4-mg cohort and 41%, 41% and 64% in the 2-mg cohort. Of those who were readministered the original baricitinib dose, the proportions of patients who recaptured vIGA-AD ® 0/1/2 among the continuous dosing, downtitration, and treatment withdrawal groups were 80%, 85% and 88% in the 4-mg cohort and 90%, 56% and 86% in the 2-mg cohort, respectively. Conclusions: Baricitinib allows flexibility for patients to downtitrate or stop treatment. For patients who downtitrated treatment, the majority maintained efficacy through 16 weeks. Most patients who lost efficacy with downtitration or treatment withdrawal achieved clinically relevant efficacy upon readministration of their original dose. Abstract : Baricitinib, an oral, selective Janus kinase (JAK)1/2 inhibitor, demonstrated long-term efficacy in moderate-to-severe atopic dermatitis (AD) in an ongoing, double-blind, Phase 3, long-term extension study, BREEZE-AD3 (NCT03334435). Baricitinib allows flexibility for patients to downtitrate or stop treatment. For patients who downtitrated treatment, the majority maintained efficacy through 16 weeks. Most patients who lost efficacy with downtitration or treatment withdrawal achieved clinically relevant efficacy upon readministration of their original dose.